Celiac Disease and Wheat Intolerance Syndrome: A Critical Update and Reappraisal. Issue 1 (January 2017) - Jericho, Hilary; Assiri, Asaad; Guandalini, Stefano
Abstract : ABSTRACT: Since the first description of celiac disease (CeD) by Samuel Gee in 1888 and the later "miraculous discovery" that bread was responsible for this condition following World War II in Europe, there has been an exponential growth of knowledge regarding CeD. Just when we thought that we knew everything there was to know about it, the disease is, however, offering new challenges, with its presentation having significantly morphed over the years from cases of overt gastrointestinal symptoms, malnutrition, and atrophic villi on duodenal biopsies to that of largely extraintestinal, subtle, or mild symptoms. Along with these changes, unexpectedly a new parallel entity appeared a few years ago and is gaining ground: the so-called nonceliac gluten sensitivity, an improper name because it should actually be referred to as wheat intolerance syndrome given that the role of gluten in all such cases is far from demonstrated and the implication of an immune involvement suggested by the term "sensitivity" is still unfounded. Lastly, wheat can be an offender also through an immunoglobulin E-mediated allergy, whose presence must also be evaluated and ruled out in selected cases. The practicing physician is therefore now challenged with the task of discerning which patients need to be assessed for one or the other of these disorders, and how. This review aims at providing an updated, critical reassessment of these 2 entities.